Burnout in relation to gender, educational attainment, and experience among Malaysian ELT practitioners - Mukundan, Jayakaran; Khandehroo, Koroush (The Journal of Human Resource and Adult Learning, 2009)
This study focused on a group of English language teachers’ burnout (N=120) with reference to their demographics of sex, teaching experience and educational level. The findings showed that burnout was evident among Malaysian English teachers at high levels in all dimensions. In addition, experience and educational level among males and females demonstrated significant relations with emotional exhaustion, depersonalization, and reduced personal accomplishment. The findings of this study might help school system administrators regard such demographic factors as crucial in recruitment decision makings and retention programs.